Pengaruh Pemberian Flavor Pada Produk Minuman Kopi Terhadap Kepuasan Pelanggan Di Eighteen Coffee Jakarta - Martinus Hia; Donant Alananto Iskandar (STREAMING, 2026)
This study examines how adding flavors (vanilla, butterscotch, palm sugar) to espresso‑based beverages affects customer satisfaction at Eighteen Coffee Jakarta. Drawing on a short survey of 50 customers, field observations, brief interviews, and limited recipe trials, we describe perceived taste balance, aroma, and texture as key drivers of satisfaction among 20–35‑year‑old customers. Original Oat Baby Latte (oat milk, butterscotch, vanilla) was favored for its smoothness but considered “too light” by some; Craft Latte Palm Sugar (palm sugar, robusta espresso) pleased those preferring stronger profiles yet was sometimes “too sweet.” A modified Craft Latte (arabica espresso with vanilla and butterscotch) received the most positive responses for balanced sweetness, cleaner aftertaste, and “premium” aroma. We discuss implications for flavor development, recipe standardization, and barista training to improve consistency and loyalty.